Iron Deficiency Anemia: The Utility of Upper Gastrointestinal Endoscopy and Histopathology - Al-Hamwandi, Adnan MH; Al-Dulaimi, Yaseen H; Al-Doori, Ali M; Al-Ani, Saad S; Al-Mashhdan, Azhar AJ (AL-Kindy College Medical Journal, 2007)
Background: occult blood loss must be considered as apossible cause in every case of iron deficiency anemia.Objective: to evaluate upper gastrointestinal endoscopyin finding a potential cause for iron deficiency anemiaamong children in Al-Anbar governorate.Methods: Twenty five children aged 2-14 years, referredto the gastroenterology unit in Al-Ramadi General Hospitalfor upper gastrointestinal endoscopy had iron deficiencyanemia. Fiberoptic endoscopy was used under generalanesthesia and endoscopic tissue biopsies were taken from22 patients for histopathological examination.Results: The main presenting signs and symptoms werepallor, abdominal pain, and stunting. The uppergastrointestinal endoscopy showed thinning of duodenalfolds & serrated mucosa in 8 (32%), duodenal ulcer in 3(12%), esophageal varices in 1 (4%), nodular gastritis in 1(4%), and reflux esophagitis in1 (4%), with a yield rate of56%.While tissue biopsies revealed histopathological findingssuggestive of celiac disease in 12 (48%), Giardia lamblia in2 (8%), Helicobacter pylori gastritis in 1 (4%), andesophagitis in 1 (4%). There was a significant associationbetween the endoscopic finding of thinning of duodenalfolds and serrated mucosa and the histopathologicalfinding suggestive of celiac disease, P